Peran Self-Determination dalam Meningkatkan Ketekunan Belajar Mahasiswa di Era Digital - Siti Badriah; Surawan Surawan (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
This study aims to examine the role of Self-Determination in improving students' learning persistence in the digital era. Self-Determination Theory explains that long-lasting learning motivation arises from within the individual, which is influenced by the fulfillment of three basic psychological needs: autonomy, competence, and relatedness. Amidst the challenges of the digital era, such as social media distractions, students are required to have internal motivation to remain diligent in learning. Through a qualitative approach, the researcher interviewed five students in depth. The results showed that students were able to maintain learning persistence because of personal goals, parental support, and previous academic success experiences. The three aspects of Self-Determination have been shown to play an important role in shaping students' learning persistence despite facing digital disruptions. This study shows the importance of strengthening internal motivation to support learning success in the digital era.